Secure and private distribution of online video and some related cryptographic issues - BAO, Feng (Institutional Knowledge at Singapore Management University, 2001)
With the rapid growth of broadband infrastructure, it is thought that the bottleneck for video-on-demand service through Internet is being cleared. However, digital video content protection and consumers privacy protection emerge as new major obstacles. In this paper we propose an online video distribution system with strong content security and privacy protection. We mainly focus on the study of security and privacy problems related to the system. Besides presenting the new system, we intensively discuss some relevant cryptographic issues, such as content protection, private information retrieval, super-speed encryption/decryption for video, and PKC with fast decryption etc. The paper can be viewed as one that proposes practical solutions to real life problems, as well as one that presents applied cryptography research.